1993
DOI: 10.1139/b93-062
|View full text |Cite
|
Sign up to set email alerts
|

Croissance rythmique endogène de la feuille de Guarea guidonia (Méliacées): Étude préliminaire expérimentale

Abstract: The composed pennate adult leaf of Guarea guidonia (Meliaceae) has a multiannual rythmic growth shown by the successive sequential setting of leaflet pairs. This is demonstrated at the level of the foliar central vein by the differentiation of periodic rings in the wood. Microsurgically isolated foliar primordia produced large leaves, the tops of which supported several foliar sequences. Early removal of foliar primordia suppressed the endogenous rythmic growth pattern and the functioning of the foliar apex be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…I observed similar juvenile leaf form in seedlings of C. weinlandii and vigorous sucker shoots of C. ceramicus, C. macranthus and C. trichocladus . Juvenile leaves with a terminal pinna were also reported in the related Guarea (Steingraber & Fisher, 1986; Miesch & Barnola, 1993). Some vigorous shoots may produce juvenile leaf form, similar to the reversion to a juvenile phase reported in other dicotyledons (Lee & Richards, 1991).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…I observed similar juvenile leaf form in seedlings of C. weinlandii and vigorous sucker shoots of C. ceramicus, C. macranthus and C. trichocladus . Juvenile leaves with a terminal pinna were also reported in the related Guarea (Steingraber & Fisher, 1986; Miesch & Barnola, 1993). Some vigorous shoots may produce juvenile leaf form, similar to the reversion to a juvenile phase reported in other dicotyledons (Lee & Richards, 1991).…”
Section: Discussionmentioning
confidence: 83%
“…Some Chisocheton species have the seemingly bizarre feature of rachis – borne buds that produce flowers and shoots (Harms, 1917; Fisher & Rutishauser, 1990). The leaf of Guarea has the ability to root after detachment and to continue growing for one or more years (Fisher, 1992; Miesch & Barnola, 1993). These features are unusual and, taken by themselves, might support the concepts of ‘fuzzy morphology’ or ‘partial homology’ offered by Rutishauser & Isler (2001), Rutishauser & Sattler (1985, 1989), and Sattler & Jeune (1992).…”
Section: Discussionmentioning
confidence: 99%
“…Leaves share developmental processes with stems. In Chisocheton and Guarea (Meliaceae) there are compound leaves that show indeterminate growth combined with seasonal growth increments due to an apical meristem at the leaf tip (Fisher and Rutishauser, 1990 ;Miesch and Barnola, 1993). Thus, such ' leaves ' share developmental processes with distichous shoots.…”
Section: Rele Ance Of Continuum and Process Morphologymentioning
confidence: 99%
“…Some leaves are, however, perennial and possess an apical meristem that continues to produce new leaflets as the leaf elongates (indeterminate growth). This is the case in the tropical genera Guarea and Chisocheton (Corner, 1964;Fisher, 1984;Fisher and Rutishauser, 1990;Miesch and Barnola, 1993). Recent evidence has also shown that determinate pinnately compound leaves may also resemble stems in their early development (Sattler and Rutishauser, 1992;Jeune and Lacroix, 1993;Lacroix and Sattler, 1994;Lacroix, 1995).…”
mentioning
confidence: 95%